Thomistic Philosophical Anthropology: An Aristotelian - Thomistic Project Author: J. C. Paul Rohan - Paul Rohan, J.C. (Faculty of Arts, University of Jaffna, 2015)
As a philosopher, St. Thomas Aquinas was emphatically Aristotelian who made an effective synthesis of Aristotelian thought and the perspective of Christian faith. His view on man and human nature is called ‘Thomistic Philosophical Anthropology’. It is Christian anthropology which views man essentially as a wholistic being composed of body and soul. Studying St. Thomas’s dependence on Aristotle is very vast and involves a lengthy research. Hence in this article references are made only to the Aristotelian roots that are found in the Thomistic philosophical anthropology. With the Aristotelian thoughts and with his own original insights, St. Thomas, using ontological principles and the Christian faith, was able to build a systematic and theoretical foundation for the concept of the soul and eventually for the human being. The human being is a complete substance comprised of matter and spirit. The substantial union, or the basic unity of the body with the soul, becomes the first affirmation in the hylomorphism of Aristotle. This substantial union of matter and form in the human reality resists all types of reductionism, whether materialistic or spiritualistic. By the body a human being has everything that is in the material world and by the soul it has access to divinity and eternity. It is this integral nature and wholeness that makes the human being, a being open to God, to the world, to fellow human beings and to all the possibilities of life. This wholistic approach is provided by the Thomistic philosophical anthropology, which is an Aristotelian - Thomistic project.
Keywords: Wholistic; Ontological; Substantial Union; Reductionism; Hylomorphism; Transcendence